La corte come istituzione educativa: la formazione del cortigiano - Laura Vanni (Firenze University Press, 2012)
The Renaissance's court has historically played a lot of functions: as a place of power, as cultural, administrative and juridical center, as home of the lord and his retinue. This institution has also the role of school of behaviour for those that were part of the court, setting from time to time, specific educational styles and behaviour models. The paper aims to analyse the pedagogical-educational function of the court, trying to show the characteristics, the modes and aims.